Variasi Bahasa pada Konten Youtube Majelis Lucu: Kajian Sosiolinguistik - Ramadhan, Ahmad Rizki; Setiyawan, Agung; Mahbubillah, Maulana Yusuf; Adira, Wafa’ Rizqiyya; Alansor, Habib Ahmad (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2024)
Many content creators convey Arabic material in a funny and witty way. It is not uncommon to convey Arabic content videos via Youtube in informal language and evem use slang to make it seem more communicative. The aim of this research is to find out the variations of Arabic found in the funny assembly youtube content, as well as find out the social language found in it. The research method used is a qualitative content analysis approach with the research subject being one of the videos from the Majelis Lucu’s youtube account. The research instrument used was observation in one of the videos with analysis of each Arabic sentence delivered and documentation to record the time the sentence was delivered in the video in question. The result of the reseach show that in the videos submitted in humorous forums, a total of 12 variation of Arabic were found, with details of 7 of language interferences, 2 language integrations, 1 code switching. And 2 arabic code mixings in youtube content. Meanwhile, the social language in the video found 2 social language with the type of slang and vulgar. The influence of conveying Arabic through youtube social media has a big impact on people’s understanding of Arabic.